GA Houses 181 : Project 2022 - Futagawa, Yoshio; Saito, Hitomi; Nakamura, Akiyo (Tokyo : A.D.A. Edita Tokyo Co., Ltd., 2022)
Ensamble Studio / Desert House ; Maki Onishi + Yuki Hyakuda / O+H / House Linked to Time of Particular Place ; Francisco Aires Mateus / House amid the Tall Corks oaks ; Nobuhiro Kitazawa / House in Koishikawa ; Grupo Aranea / Casa Fortuna ; Max Núñez / House in the Trees ; Phorm Architecture + Design / Raft House ; Cecilia Puga + Paula Velasco / Vaulted House by a Lake ; Ryue Nishizawa / I House ; Tom Wiscombe / Hare House ; Pezo von Ellrichshausen / Bear House ; Hideyuki Nakayama / A Small Planet ; Shingo Masuda + Katsuhisa Otsubo / Afloat Garden ; Christian Kerez / Hustler House ; SPBR Arquitetos / Casa quadra in Orlandia ; Cristián Izquierdo / House in Nonguén ; Sou Fujimoto / Nature Room ; OPA / Houses of the Trident 2.0 ; Alberto Kalach / Tree House ; Junya Ishigami / Ivy House ; Hiroyuki Unemori / House A/O ; Robin Donaldson / Hill House ; Satoshi Matsuoka + Yuki Tamura / Lodge in Susono ; Yo Shimada / House in Kashii ; Fran Silvestre / Roca Views Ibiza ; Kengo Kuma / Rooftop Garden ; Antonius Lanzinger / Viola da casa ; Erika Nakagawa / Yagoto House ; Katsufumi Kubota / MR-House ; Andra Matin / MR Residence ; Suppose Design Office / House in Yokosuka ; Hirotaka Kidosaki / Weekend Retreat in Shichirigahama ; Takashi Fujino/Ikimono Architects + Sunao Koase, Yu Yamada, Rei Oshima/Snarks Inc. / Amanoiwato ; Mathias Klotz & Edgardo Minond / Houses in Patagonia ; Suzuko Yamada / Hebi ; Tomohiro Hata / House in Mukoshi ; Peter Stutchbury / Humble House ; Alphaville Architects / Hutte in Koyasan ; Hiroyuki Arima / Adhesion with the Woods ; Gruposp / Cicade Jardim House 2 ; Taichi Mitsuya / House in Kamakurayama ; Sean Godsell / House in Rye (Second Scheme) ; Keisuke Maeda / Obi=Yon - Shiroobi ; Takeshi Hirobe / 303 ; Yasushi Horibe / House in Inasa ; Wespi de Meuron Romeo Architects / New House in Barbengo ; Shigeru Fuse / House in Doujyou-Kita ; Gurjit Singh Matharoo / City Walled ; Makoto Takei + Chie Nabeshima / TNA / A Project
Studio Tonton / RK House ; Manuel Aires Mateus / House in Quinhão do Barranco
boek